ヒガシ オングルトウ エンガン デノ ヒョウカ センスイ チョウサ ホウコク - 渡辺, 研太郎; ワタナベ, ケンタロウ; 中嶋, 泰; ナカジマ, ヤスシ; 内藤, 靖彦; ナイトウ, ヤスヒコ; Watanabe, Kentaro; Nakajima, Yasushi; Naito, Yasuhiko (1982)
P(論文) 1981年1月15日から31日にかけて, 昭和基地付近の3点(底質は砂地と岩場)において, 第21次南極地域観測越冬隊および第22次夏隊に参加した3名が, SCUBA(自給気潜水器)を用いた生物調査を行った。潜水回数は15回, 延べ33回・人。各回の潜水時間は約45分, 最大55分で, 最大潜水深度は18mであった。使用したドライスーツをはじめとする潜水機材は, 南極の夏季の潜水作業には十分な性能を備えていることが判明した。調査の結果, これまでトラップでは採集できなかったナンキョクツキヒガイなどのろ過食性生物を含め, 約200点の底生生物を採集した。このほか35mmカラーフィルムで約250こま, 8mmカラーフィルムで約400フィートの水中写真に生物の生態を記録し, 所期の目的を達成した。 Biological surveys of benthic and ice-associated communities by SCUBA diving were performed on 15-31 January, 1981,at three points near Syowa Station (69°00′S, 39°35′E). Three biologists of the 21st and the 22nd Japanese Antarctic Research Expedition (JARE) participated in the surveys. Fifteen dives were made and the average duration of a dive was 45 min (max. 55 min). The maximum diving depth was 18m. Diving gears including the dry suit, proved to be sufficient for the cold in the summer season of Antarctica. About 200 specimens were collected including benthic animals which were new to Syowa Station. Underwater pictures were also taken to record the aspects of benthic and ice-associated communities, and the recorded films amounted to about 250 frames of 35mm color filmslides and about 400 feet of 8mm color cine film. Some observations of divers in the Antarctic shallow waters are briefly commented. departmental bulletin paper